COMMAND OF TONTEMBOAN LANGUAGE USED BY PEOPLE IN SULUUN - Rumondor, Eunike; Olii, Sanerita T.; Kamagi, Sarah (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This research is written as an attempt to find out the types and functions of commands of Tontemboan Language that used by people in Suluun. This research used qualitative method. The subject of this study is Tontemboan language that is used by its speakers who live in Suluun. This subject is the source of data from whom information about the command in Tontemboan language will be obtained. The data were collected by talked with native speakers, and the other references such as journals, books and internet sources which related and relevant to this research. The result of this study is command divided into two which is direct and indirect command. Mostly, the people in Suluun used direct command. Based on this research, it can be suggested that the readers are invited to preserve the local language. The local language is important to the next generation especially for the young generation in Suluun. There are many people have declined to use it or even ashamed. But then there are young people use the Tontemboan language daily. People must be motivated to use local language until the tourist become interested to studying the local language. Because the local language is the identity of each area in Indonesia.